Design and Application of Automatic Control System for Fully Mechanized Mining Face in Coal Mine - Zhi Yuan; Huanlei Chi; Yan Cao (Advances in Multimedia)
In order to improve the automatic control effect of fully mechanized mining face in coal mine, this paper combines the literature research method to analyze the disadvantages of traditional research and combines the demand analysis to analyze the structure of the automatic control system of fully mechanized mining face in coal mine. Moreover, this paper uses an improved algorithm to improve the system performance, uses the analytical approximation method to calculate and eliminate the loading phase of the fourth-order input and output equal-length cavity filter and the fourth-order input and output unequal-length cavity filter, and obtain the correct coupling matrix. In addition, this paper uses the genetic algorithm to calculate and eliminate the loading phase of the sixth-order input-output equal-length cavity filter and the sixth-order input-output unequal-length cavity filter. In addition, after the system is constructed, the performance analysis of the system can be known through experimental research. The research results show that the automatic control system of fully mechanized mining face in coal mine proposed in this paper has a good intelligent control effect.